Efficacy of the Tribulus food supplement used by athletes - MILAŠIUS, Kazys; PEČIUKONIENĖ, Marija; DADELIENĖ, Rūta; SKERNEVIČIUS, Juozas (Acta medica Lituanica, 2010)
Introduction. Tribulus is a popular food supplement used by a big number of athletes. It is made from the puncture (Tribulus terrestris) plant growing in the Mediterranean region. Tribulus terrestris increases activity of protein synthesis and muscular mass and facilitates recuperation after physical loads. The analysed literature sources present clinical researches on Tribulus, however, data on the efficacy of this food supplement to athletes’ body are not sufficient.The aim of the research was to establish the influence of the Tribulus food supplement on athletes’ physical development, physical working ability and aerobic capacity as well as on some blood biochemical indices.Materials and methods. The sample of the research included thirty-two 20–22-year-old athletes. The experimental group consisted of 20 individuals who used one capsule of Tribulus of the Optimum Nutrition Company (USA) in the morning and two capsules in the evening for the next 20 days. The control group consisted of 12 individuals who did not consume any food supplement. The physical development, physical working ability and aerobic capacity of the athletes were measured.The research results showed that the Tribulus food supplement increased mixed anaerobic alactic glycolytic muscular power at 30-s work and reduced lactate concentration in the blood.Conclusions. The Tribulus food supplement has a positive influence on athletes’ anaerobic alactic glycolytic power and aerobic capacity when energy is produced in the aerobic way.Keywords: Tribulus food supplement, physical development, muscular power, aerobic capacity